Language Changes in Schizophrenia: A Limited Replication - Morice, Rodney; McNicol, Don (Schizophrenia bulletin, 1986)
Similar changes in the spoken language of schizophrenic patients were demonstrated in two separate studies. Schizophrenic patients used less depth of clausal embedding and fewer reduced relative clauses; they uttered more semantically deviant sentences and were more dysfluent than either manic patients or control subjects. They appeared to demonstrate a language impairment characterized especially by reduced syntactic complexity. Four linguistic variables in a discriminant analysis produced an overall diagnostic confidence for schizophrenia in "grouped" subjects of 87 percent, replicating at 83 percent for "ungrouped" subjects from a separate study. These results demonstrate the stability of language changes in schizophrenia, together with acceptable levels of diagnostic sensitivity and specificity. Currently, the possible diagnostic utility of language analysis is constrained by its time-consuming nature. The issue of whether the language changes represent a specific (linguistic) or general cognitive impairment is being addressed in a second phase of the current study.